PENGARUH ELEMEN INTERIOR STUDIO ANIMAXX TERHADAP PROSES PEMBELAJARAN - Ronald Justice; Atik Suprapti; Budi Sudarwanto (Jurnal Arsitektur ARCADE, 2021)
Abstract: Dynamic education must be able to follow the progress of the times that continue to develop. The demands of 21st century skills have an impact on improving the quality of vocational education through innovation of educational facilities and infrastructure that are in line with sustainable development goals in realizing quality education. To achieve this goal, the school seeks to improve the quality of learning through structuring the interior elements of the learning space. The purpose of this study was to describe the interior elements of Animaxx studio in terms of lighting, color, shape, and material aspects and to determine the effect of interior elements on the learning process in terms of motifs, affective, and learning achievement. Combined research methods (mix methods) were used in this study, quantitative methods were used to collect data about user perceptions of interior elements and responses to motives, affective, and learning achievement through questionnaire collection. Strengthened by qualitative methods with data collection techniques through interviews, literature studies and direct observation to the object of research. The data collected were analyzed descriptively and hypothesis testing through regression analysis. From this research, it was found that the effect of user perception on Animaxx studio interior elements had an effect on motive and affective. While the motive and affective simultaneously affect the achievement of learning. So it can be concluded that there is a significant influence between Animaxx studio interior elements on the learning process.Abstrak: Pendidikan yang dinamis harus dapat mengikuti kemajuan zaman yang terus berkembang. Tuntutan keterampilan abad 21 berdampak pada peningkatan mutu pendidikan kejuruan melalui inovasi sarana dan prasarana pendidikan yang selaras dengan tujuan pembangunan berkelanjutan dalam mewujudkan pendidikan berkualitas. Maka dari itu sekolah berupaya meningkatkan kualitas pembelajaran melalui penataan elemen interior ruang pembelajaran. Tujuan penelitian ini adalah mendeskripsikan elemen interior studio Animaxx ditinjau dari aspek pencahayaan, warna, bentuk, dan material dan mengetahui pengaruh elemen interior terhadap proses pembelajaran yang dilihat dari motif, afektif, dan ketercapaian pembelajaran. Metode penelitian kombinasi (mix methods) digunakan dalam penelitian ini, metode kuantitatif digunakan untuk mengumpulkan data tentang persepsi pengguna terhadap elemen interior dan respon tentang motif, afektif, dan ketercapaian pembelajaran melalui pengumpulan kuesioner. Dikuatkan metode kualitatif dengan teknik pengumpulan data melalui wawancara, studi literatur dan observasi langsung ke obyek penelitian. Data yang terkumpul dianalisis secara deskriptif dan uji hipotesis melalui analisis regresi. Dari penelitian ini diperoleh hasil penelitian adanya pengaruh persepsi pengguna terhadap elemen interior studio Animaxx berpengaruh terhadap motif dan afektif. Sedangkan motif dan afektif secara simultan berpengaruh terhadap ketercapaian pembelajaran. Sehingga disimpulkan ada pengaruh signifikan antara elemen interior studio Animaxx terhadap proses pembelajaran.